(untitled) (Journal of Asian Development Studies, 2026)
One in three women globally experienced physical or sexual violence in their lifetime (World Health Organization, 2021), but how is this trauma expressed when words fail? Modern women’s literature is more and more tending to the body as a central site of telling, a shift that is crucial to the way trauma is not only lived, but told. Although literary trauma studies have conventionally been concerned with such memory domains as the psychological and verbal memory, there is a substantial gap in terms of the exploration of the embodied aspects of trauma. This research fills that gap by drawing on five contemporary autobiographical texts, the works of women in 2019 2022, excerpted by the purposive sampling method, with their thematic emphasis on trauma and embodiment. Supported by the NVivo coding, narrative mapping, and an embodiment grid, this research finds four recurring themes by qualitative textual analysis. Archive, Voice and Silence, Reclamation, and Intersectionality. The major theme – Reclamation – shows how writers use narrative to demand bodily agency and healing. Findings note that trauma is not just a mental impression but a body based experience, told in mutilated syntax, sensory metaphor, and disrupted chronology. This research extends the feminist trauma theory and trauma-informed literary pedagogy with a replicable analytical model. Recommendations are to incorporate trauma-aware reading frameworks in literature curriculum and memory skills and trauma-aware practices across literary and therapeutic arena.